La crisis del 98 y la autonomía universitaria - Sánchez Santiró, Ernest (Millars. Espai i Història, 2018)
The crisis of 1898 was constituted in a various contradictions catalyst that were managed to the beginning of the restoration by Alfonso Xli. With the rout of the democratic action of the Sexenio the Spanish university saw paralysed the dfferent autonomic iniciatives that only the crisis of the system of the restoration ending tite XIXth century permitted to return to outline. In this context, thefacully of the Universily of Valencia outlined in 1899 a reform project of university autonomy that was submitted to the Ministerio de Fomento and to ah the universities of the State, being considered preceding of the iniciatives of García Alix (1900) and Romanones (1902).